Analysis of Serum Creatinine Levels, Blood Pressure and Grade of Hypertension of Chronic Disease Management Program Participants - Tanjung, Asbar; Nurhidayah, Ika; Maulidayanti, Sharfina; Br Situmorang, Ing Mayfa (Medical Laboratory Technology Journal, 2025)
Indonesia is one of the countries with the highest number of cases of hypertension in the world; the predominant patient is the elderly. In some patients with hypertension, increased blood pressure causes impaired salt and creatinine excretion, resulting in poor kidney function. A chronic disease management program is a health care system with a proactive-integrative approach to prevent further complications. The research objective is to analyze serum creatinine levels, blood pressure, and hypertension grade and determine the relationship between serum creatinine and blood pressure in chronic disease management program participants. The study subjects, 73 participants with hypertension, were obtained by purposive sampling. Patient data and hypertension grade were obtained from medical records; an auto chemistry analyzer analyzed serum creatinine. Data were analyzed using the Pearson correlation test using SPSS. Participants with hypertension fall into the elderly age (60-69 years), totalling 31 (42%); pre-elderly age (45–59 years) includes 28 (38%); and high-risk elderly age (>70 years) includes 14 (19%). Most of the participants (40 participants) fell into hypertension stage II, followed by hypertension stage I (25 participants), and only 8 participants fell into the elevated category. The mean serum creatinine of participants with Elevated blood pressure criteria was 0.89±0.178, Hypertension grade I 0.91±0.322, and hypertension grade II 0.99±0.269, illustrating a trend of increasing serum creatinine levels due to higher blood pressure criteria. Pearson correlation test shows a significant correlation between both systolic blood pressure with serum creatinine levels (p<0.05, r=0.2) and diastolic blood pressure with serum creatinine levels (p=0.007, r=0.342). There was a trend of increasing serum creatinine levels corresponding to the hypertension grade in participants. Blood pressure was significantly correlated with serum creatinine, clearly confirming that an increase in blood pressure may followed by an increase in serum creatinine.